SUBSTRATE PREPARATION SYSTEM INFLUENCE ON TILE CLADDING DURABILITY: INVESTIGATION THROUGH RESIDENTIAL BUILDING RENOVATION CASE STUDIES - Kuchinka, Veniamin (Global Prosperity, 2026)
Abstract. Abstract. Substrate preparation quality determines tile cladding system longevity in residential renovations, yet specification protocols remain empirical rather than evidence-based. This investigation quantified self-leveling compound performance variability across substrate types, computational stress analysis of localized weakness effects, and primer system evaluation under contaminated conditions typical of renovation practice. Experimental testing characterized four compound formulations on concrete, gypsum plaster, and cement-lime render substrates, documenting substrate-dependent strength variations and temporal shrinkage patterns influencing installation timing requirements. Finite element modeling analyzed tile systems over substrate weakness zones, establishing stress concentration factors and overlay thickness optimization relationships. Primer comparison under form oil and curing compound contamination identified performance differentiation absent in clean substrate testing. Results demonstrated that substrate-compound compatibility produces greater performance variation than formulation selection alone, with chemical interactions generating strength differentials. Computational analysis revealed nonlinear stress concentration scaling with weakness severity, establishing rational thickness specification methodology. Primer performance manifested primarily under contaminated conditions, with penetrating versus film-forming mechanisms exhibiting complementary capabilities across contamination types. Environmental durability testing identified moisture cycling as the dominant degradation mechanism for traditional cementitious primers. Economic lifecycle analysis validated preparation quality investment reducing total cost through extended service life despite higher initial expenditure. Research outcomes provide systematic decision framework integrating substrate assessment, material matching protocols, and thickness optimization enabling evidence-based specification for residential renovation contexts.